PERBANDINGAN BENTUK PERTUNJUKAN WAYANG KLlTIK UNDAAN KUDUS DENGAN NGEMPLAK SLEMAN - Suwondo, Suwondo (Gelar : Jurnal Seni Budaya, 2011)
Wayang klitik performance at Sleman, Yogyakarta has some differences and similarities with that at Kudus, Central Java although they came from the same source. After a long period of time, those who used to be the devotees of wayang klitik have lived in different places and the puppeteers of wayang klitik have performed a different characteristic of performance. The story and function of wayang klitik in Kudus are more dynamic because wayang klitik is thought not only as the only entertainment but also as a ritual for the surrounding society. Wayang klitik at Kudus is always performed annually as a sendang (spring) purifying ritual. Wayang klitik performance at Sleman, Yogyakarta is held in the territory with limited devotees. The inhabitants of the territory coming from the outside are usually the younger generation and educated people who are not familiar with wayang klitik. The form of Wayang klitik performance at Sleman, Yogyakarta refers to the norm (pakem) of wayang purwa that has been traditionally performed in puppetry. If there is a change in the performance, it usually has something to do with a puppeteer's own version (sanggit) and the characteristic of his performance. Wayang klitik performance at Sleman, Yogyakarta has a tendency to contain aesthetic values and it is less communicative. During the last four years, Wayang klitik at Sleman, Yogyakarta has been performed twice only so that the society tend to have little interest in it. The similarity in the form of the performance between wayang klitik at Sleman and that at Kudus is that the performance begins with a major scene (jejer). The accompanying melody (gending) for wayang klitik at Sleman is relatively more dynamic and the garap is more creative and inventive in nature. However, the performance has less close relation with the audience so that there is an impression that the performance is separated from the audience. On the other hand, wayang klitik performance at Kudus has close relation with the society. Wayang klitik performance at Kudus is more simple and has a religious impression that can be appreciated in many ways of communication and as may be required by the society. The romantic scenes performed at wayang klitik performance at Kudus is very simple in line with the society's homogenous thinking level.Key words: Wayang Klitik, function and form, comparison.